2014
DOI: 10.1257/jep.28.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Slicing Up Global Value Chains

Abstract: In this paper, we “slice up the global value chain” using a decomposition technique that has recently become feasible due to the development of the World Input-Output Database. We trace the value added by all labor and capital that is directly and indirectly needed for the production of final manufacturing goods. The production systems of these goods are highly prone to international fragmentation as many stages can be undertaken in any country with little variation in quality. We seek to establish a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
430
0
32

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 729 publications
(473 citation statements)
references
References 34 publications
11
430
0
32
Order By: Relevance
“…One study found that the foreign VA content of exports from Luxembourg was 61 % in 2011 (Foster-McGregor and Stehrer 2013 ). Interestingly, there seems to be a trend towards value being added by capital and high-skilled labour and away from less-skilled labour (Timmer et al 2014 ). The capital share in the VA of emerging economies is rising, whilst the share of low-skilled labour in their VA is declining.…”
Section: Scope and Scale Of Embodied Impactsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study found that the foreign VA content of exports from Luxembourg was 61 % in 2011 (Foster-McGregor and Stehrer 2013 ). Interestingly, there seems to be a trend towards value being added by capital and high-skilled labour and away from less-skilled labour (Timmer et al 2014 ). The capital share in the VA of emerging economies is rising, whilst the share of low-skilled labour in their VA is declining.…”
Section: Scope and Scale Of Embodied Impactsmentioning
confidence: 99%
“…A strong driver of globalisation has been the move of production to places where wages and therefore total production costs are relatively low (Timmer et al 2014 ). A large workforce in developing low-wage countries is employed to manufacture goods for exports, mostly to the developed world.…”
Section: Scope and Scale Of Embodied Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…In reality, however, all but the most basic products are an assemblage of inputs sourced from around the world. Timmer et al (2014) provided a macro-view of the Bmade in the world^phenomenon and used the World Input-Output Tables (Dietzenbacher et al 2013) to document the rapid fragmentation of production and increasing value-added share being captured by the owners of capital and highly skilled labor since the early 1990s. In addition, these researchers also noted that the developed countries increasingly specialize in functions carried out by highly skilled workers and that the developing countries have increased their specialization in capitalintensive functions.…”
mentioning
confidence: 99%
“…Pelo contrário, a montagem e a manufatura geram uma fração menor do VA. Em segundo lugar, mostrou que as cadeias de valor industriais são cada vez mais internacionalizadas e nelas perde peso o emprego menos qualificado. Por um lado, é evidente o aumento do VA estrangeiro nas cadeias de valor do mundo todo, como o caso da indústria automotiva alemã (TIMMER et al, 2013) ilustra. O deslocamento foi impulsionado inicialmente pelos custos salariais menores, e depois pela redução dos custos para coordenar atividades a distância, pelos avanços nas tecnologias de informação e comunicação, etc.…”
unclassified